2018
DOI: 10.1093/bioinformatics/bty481
|View full text |Cite
|
Sign up to set email alerts
|

Accurate prediction of protein contact maps by coupling residual two-dimensional bidirectional long short-term memory with convolutional neural networks

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
234
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(235 citation statements)
references
References 41 publications
1
234
0
Order By: Relevance
“…Since training deep learning network requires a large number of training samples, we employed the dataset curated in 2017, as used in our previous study (Hanson, et al, 2018). The dataset is consisted of 12450 nonredundant chains with resolution < 2.5Å, R-factor < 1.0, sequence length ≥ 30, and sequence identity ≤ 25% from the cullpdb website.…”
Section: Datasetsmentioning
confidence: 99%
“…Since training deep learning network requires a large number of training samples, we employed the dataset curated in 2017, as used in our previous study (Hanson, et al, 2018). The dataset is consisted of 12450 nonredundant chains with resolution < 2.5Å, R-factor < 1.0, sequence length ≥ 30, and sequence identity ≤ 25% from the cullpdb website.…”
Section: Datasetsmentioning
confidence: 99%
“…In CASP12 and previous CAMEO tests we have demonstrated that deep ResNet can greatly improve contact prediction 6,[8][9][10] and that even without time-consuming conformation sampling, contacts predicted by deep ResNet can result in correct folding of (even membrane) proteins without detectable homology in PDB 11 . Afterwards, the power of deep convolutional neural network has been further validated by other research groups who have reimplemented similar deep networks for contact prediction [12][13][14] . Although contact prediction itself is an important problem that needs further research, we have switched our focus from contact to distance prediction and accordingly distance-based protein structure modeling.…”
Section: Introductionmentioning
confidence: 99%
“…[86][87][88] Recurrent architectures have also been used in contact prediction. 48,89 More recently, a recurrent architecture has been used to model tertiary structure. 90 This latter method has the attractive property of being end-to-end differentiable, meaning that all parts of the process from taking in the input features to predicting 3D coordinates (via predicted torsion angles) can be simultaneously optimized during the NN training process.…”
Section: Discussionmentioning
confidence: 99%